The Impact of ACTN3 Gene Polymorphisms on Susceptibility to Exercise-Induced Muscle Damage and Changes in Running Economy Following Downhill Running - de Lima, Leonardo Coelho Rabello; Bueno Junior, Carlos Roberto; de Oliveira Assumpção, Claudio; de Menezes Bassan, Natália; Barreto, Renan Vieira; Cardozo, Adalgiso Coscrato; Greco, Camila Coelho; Denadai, Benedito Sérgio (Frontiers in Physiology, 2021)
The aim of this study was to investigate if ACTN3 gene polymorphism impacts susceptibility to exercise-induced muscle damage (EIMD) and changes in running economy (RE) following downhill running. Thirty-five healthy males were allocated to two groups based on their ACTN3 gene variants: RR, and X allele carriers. Neuromuscular function (knee extensor isometric peak torque, rate of torque development and countermovement and squat jump height), indirect markers of EIMD (muscle soreness, mid-thigh circumference, knee joint range of motion and serum creatine kinase [CK] activity) and RE (oxygen uptake, minute ventilation, blood lactate concentration and perceived exertion) during 5-minute runs at a speed equivalent to 80% of individual maximal oxygen uptake speed were assessed before, immediately after and 1-4 days following a 30-minute downhill run (-15%). Neuromuscular function was compromised (p<0.05) following downhill running with no differences between groups, except for IPT, which was more affected in RR individuals compared to X allele carriers immediately (-24.9±6.9% vs -16.3±6.5%, respectively) and 4 days (-16.6±14.9% vs -4.2±9.5%, respectively) post-downhill running. EIMD manifested similarly for both groups except for serum CK activity, which was greater for RR (398±120 and 452±126 U.L-1 at 2 and 4 days following downhill running, respectively) compared to X allele carriers (273±121 and 352±114 U.L-1 at the same time points). RE was compromised following downhill running (16.7±8.3% and 11±7.5% increases in oxygen uptake immediately following downhill running for RR and X allele carriers, respectively) with no difference between groups. We conclude that although RR individuals appear to be more susceptible to EIMD following downhill running, this does not extend to changes in RE.